Cosmetic bone contouring. Issue 4 (August 2017) - Rodman, Regina
Abstract : Purpose of review: In recent years, cosmetic bone contouring surgery has become increasingly popular, especially in East Asian countries. These procedures are also being requested by patients in the United States at an increasing rate. The purpose of this study is to provide an overview of what is involved with these procedures and their potential complications. Recent findings: In some cultures, a wide jaw and a square face are aesthetically unpleasing, whereas an ovoid or 'melon seed face' is thought to be feminine, delicate and beautiful. Mandibular angloplasty, mandibular lateral cortex excision, reduction malarplasty, as well as genioplasty may be performed to alter the facial contour and bring about dramatic results. Summary: Whether a surgeon choses to incorporate these procedures into practice or not, the craniofacial surgeons should be familiar with the procedures as well as the potential complications.